AEROBIC EXERCISE COMBINED WITH TECHNIQUES PROGRAME CAN BE INCREASED GROUNDSTROKE SKILL OF TENNIS ATHLET - Nasrulloh, Ahmad (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2012)
Professional tennis athletes should be able to master all the basic techniques of playing tennis and having physical fitness. Therefore, it is necessary to get an exercise that can give meaning to the skills and physical fitness. One of the proper exercises is with aerobic exercise combined with the technique.Aerobic exercise program combined with techniques is: (1) a number of players consisting of six to seven people with backward sequential formation techniques performing forehand and backhand groundstrokes served by the trainers, (2) coaches pass eight balls toward the forehand, backhand, forehand, backhand in sequence, (3) after the player completes an eight stroke strike then runs around the tennis court and while collecting the ball that has been hit, ( 4) the next player gets back to its previous position and ready for the next shot, (5) perform with three times frequency of exercise a week, (6) perform with the exercise intensity between 75% - 85% of maximum heart rate, (7) perform for 25 minutes per meeting, (8) the time interval is 24-48 hours, and (9) the periodization on stages of early preparation.Aerobic exercise combination with a technique given by a measurement, regularly and programmed can help improving physical fitness and skills of forehand and backhand groundstrokes for tennis athletes. Backhand skills may be changed naturally better than forehand techniques, so that it is given the same portion of exercise that will increase differently. Keyword: aerobic exercise, groundstroke techniques, tennis